Dual nickel- and photoredox-catalyzed enantioselective desymmetrization of meso anhydrides and C-O bond activation via phosphines and photoredox catalysis - Stache, Erin Elizabeth, author; Rovis, Tomislav, advisor; Doyle, Abigail G., advisor; Chen, Eugene, committee member; McNally, Andy, committee member; Reynolds, Melissa, committee member; Kipper, Matt, committee member (Colorado State University. Libraries, 2018)
Described herein is the application of photoredox catalysis in the development of new synthetic methods. A dual nickel- and photoredox catalyzed desymmetrization of meso succinic anhydrides was developed to generate stereodefined cis keto-acids in high enantioselectivity and diastereoselectivity. The approach employed benzylic radicals as a coupling partner, generated from a photoredox catalyzed single-electron oxidation of benzylic trifluoroborates using an inexpensive organic dye. A unique epimerization event was discovered and the degree of epimerization was rendered tunable by changing catalyst loadings to ultimately form the trans diastereomer preferentially in high enantioeselectivity. A method for the C–O bond activation of aliphatic alcohols and carboxylic acids was developed using phosphines and photoredox catalysis. This novel reaction platform was used to generate aliphatic or acyl radicals directly from benzylic alcohols and aliphatic and aromatic acids, and with terminal hydrogen atom transfer, afforded the desired deoxygenated alkanes and aldehydes. Additionally, the intermediate acyl radicals could be intercepted in an intramolecular cyclization reaction to generate new lactones, amides and ketones.
Keywords: nickel catalysis; photochemistry; organic synthesis; asymmetric catalysis